2018
DOI: 10.4103/jnsbm.jnsbm_111_17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical and magnetic resonance imaging profile of pituitary macroadenoma: A prospective study

Abstract: Background:Pituitary macroadenoma is a common tumor of middle-aged people. Magnetic resonance imaging (MRI) is the investigation of choice for its evaluation. Various parameters regarding the extent, consistency, and contrast uptake can be studied and a noninvasive diagnosis is possible.Aims and Objectives:To study the MRI features and extent of pituitary macroadenomas.Materials and Methods:We studied clinical and MRI features of 33 patients of all age groups and both sexes with pituitary macroadenomas who pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…36 Macroadenomas most often appear heterogeneous and hyperintense on T2-weighted images and isointense on T1-weighted images. 37 These imaging findings were noted in our patient, further supporting the radiographic diagnosis of PA rather than metastatic melanoma initially. Although features such as hemorrhage and invasion into the cavernous sinus may help to distinguish a pituitary metastasis from an adenoma, these characteristics are not specific to metastasis.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…36 Macroadenomas most often appear heterogeneous and hyperintense on T2-weighted images and isointense on T1-weighted images. 37 These imaging findings were noted in our patient, further supporting the radiographic diagnosis of PA rather than metastatic melanoma initially. Although features such as hemorrhage and invasion into the cavernous sinus may help to distinguish a pituitary metastasis from an adenoma, these characteristics are not specific to metastasis.…”
Section: Discussionsupporting
confidence: 81%
“…38 Additionally, in a prospective study of patients with pituitary macroadenoma, almost half of patients (45.45%) were noted to have imaging features of intratumoral hemorrhage. 37 The level of variability in tumor presentations and imaging characteristics requires a final diagnosis to be made histopathologically.…”
Section: Discussionmentioning
confidence: 99%
“…Gupta K. also reported that majority of macroadenoma's had supra sellar extension (72.7%). [29]. Limitation of our study was that number of patients was less.…”
Section: Discussionmentioning
confidence: 88%
“… 6 Targeted radiotherapy to the pituitary gland, particularly stereotactic radiotherapy, is associated with a significant improvement in survival time (16 months) compared to that of untreated patients (6 months). 8 Nevertheless, unless effective targeted treatment is available for the primary malignancy, the prognosis is still poor, as survival is determined by the primary malignancy itself rather than the pituitary lesion.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, differentiating a pituitary adenoma from a collision tumor based on imaging studies alone was challenging: intratumoral hemorrhage and loss of the posterior bright spot on pituitary MRI are also observed in pituitary adenomas and are not specific to pituitary metastases. 8,9 However, metastasis to the pituitary gland should be suspected in the presence of aggressive bony destruction, rapid growth with a relatively normal pituitary fossa, involvement of the infundibulum, the appearance of a dumbbell-shaped tumor with a clear indentation at the level of the diaphragma sellae, or the presence of additional intracerebral metastatic lesions. 10 The definitive diagnosis of collision tumors, therefore, is made through histopathologic examination of the sellar mass, mostly from tumors resected during pituitary surgery or rarely, from postmortem examination.…”
Section: Statement Of Authorshipmentioning
confidence: 99%